Penerapan Program Matrikulasi Biologi Umum Fakultas Ilmu Pendidikan Tahun 2016/2017 [On The Implementation of General Biology Matriculation Program Faculty of Education In 2016/2017] - Meilane Sahetapy (Universitas Pelita Harapan, 2018)
Matriculation is an adjustment program intended to accelerate the adaptive ability of students’ academic and non-academic skills at the beginning of study at a university. The university is authorized to design and create its own forms of matriculation programs in accordance with the ability of university and the conditions of prospective students who have been accepted. The purpose of the Matriculation Program in the Biology Education Study Program is to help students to better understand foundational knowledge, especially in general Biology. This study was an evaluative research, and data were collected using questionnaires and interviews. The total sample was 48 students. The results show that matriculation is important for participants with diverse educational backgrounds. The result of this study should be developed by evaluating suggestions and inputs for the development of matriculation activities in the next academic year.BAHASA INDONESIA ABSTRAK: Matrikulasi adalah program penyesuaian yang dimaksudkan untuk mempercepat kemampuan adaptasi akademik maupun non-akademik mahasiswa di perguruan tinggi yang bersangkutan. Perguruan Tinggi pelaksana diberi kewenangan untuk merancang dan mengkreasi sendiri bentuk program matrikulasi sesuai dengan kemampuan perguruan tinggi dan kondisi calon mahasiswa yang diterima. Tujuan Program matrikulasi pada. Program Studi Pendidikan Biologi adalah agar mahasiswa lebih memahami pengetahuan dasar khususnya pada mata kuliah Biologi Umum. Penelitian ini menggunakan penelitian evaluatif. Data dikumpulkan dengan kuesioner dan wawancara. Jumlah sampel 48 mahasiswa. Hasil penelitian menunjukkan bahwa matrikulasi penting bagi peserta dengan latar belakang pendidikan yang beragam. Hasil penelitian ini perlu dikembangkan dengan mengevaluasi saran dan masukan untuk pengembangan kegiatan matrikulasi pada tahun akademik berikutnya.